'Wish you were here': Contemporary views of the Outer Hebrides. Issue 1 (1st April 2018) - Jaramillo, George S.
The idealized image of the Outer Hebrides includes wind-swept beaches, isolated peat-covered moors and craggy mountain cliff tops abounding with wildlife. These images are reproduced in countless tourist postcards and websites to entice visitors to visit, explore and of course spend their money on the islands. At the same time, these images create a certain 'expectation' of the islands that not only promotes a particular 'way of seeing' the landscape but perpetuates a dominant narrative of the 'wild' wind-swept islands. This visual project challenges these notions of 'nature', wilderness and folk heritage by accepting alternative and 'minor histories' of the landscapes. In a subversive nod to the travel postcard, this article explores contemporary issues of island life and landscape through unconventional illustrations of island postcards by its residents and the author. These postcards are themed around contemporary Hebridean issues including isolation, community, landscape and family. The project contemplates an innovative approach to illustration, as ethnographer and critical tourist. Therefore, looking at the fragmentary constellation of images made about the islands that challenges the notion of a 'wild' romantic island place, and offering insight into how identity, place and heritage are developed within the region.